A CASE STUDY ON ANDHRA PRADESH AND TELANGANA STATES TOWARDS CULTURAL TOURISM - B. Swapna, Dr. M. Thyagaraju (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
India is fast becoming a necessary tourism location in the world. International arrivals contacted 5 thousand yearly. The initiative "Astonishing India" which include the best that India has to offer to the vacationers has now produced all over the world interest. The proactive programs of the Authorities of India are promoting tourism in India. Andhra Pradesh is the leading state in the nation in bring in an optimum wide array of residential vacationers. In 2012, 157 million residential tourists observed Andhra Pradesh. This notes an improvement of 14% over 2011. Telangana topographically and typically possesses a range of tourist attractions featuring hills, creatures, jungles, barrier and also holy places. This place has a wealthy cultural heritage and is identified for its very own bountiful file, type as well as likewise society. This region has all the required top qualities for becoming an effective site visitor location in India. The climate is normally tropical. This paper briefly provides a case study on andhra pradesh and telangana states towards cultural tourism.